A novel absorbent body of environmentally friendly composite fiber sanitary napkin and its preparation method and application

Through the three-layer fiber mesh structure and microwave cross-linking technology, combined with antibacterial and temperature-sensitive materials, the shortcomings of sanitary napkins in absorption performance, comfort and anti-leakage are solved, and an efficient, comfortable and environmentally friendly sanitary napkin design is achieved.

CN120360781BActive Publication Date: 2025-09-16LITTLE NURSE (TIANJIN) TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510888800.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-30
Publication Date
2025-09-16
Estimated Expiration
2045-06-30

AI Technical Summary

Technical Problem

Existing sanitary napkins have deficiencies in absorption performance, comfort and side leakage prevention, especially when used for a long time or during exercise, which can easily lead to uneven liquid distribution and side leakage. The traditional design also sacrifices the lightness and comfort of the product.

Method used

It adopts a three-layer fiber mesh structure and a gradient pore design composed of ES fiber and bamboo-based modified viscose silk. It forms a tight connection through microwave cross-linking and axial pressure, combined with chitosan-coated nanosilver and thermosensitive hydrogel microspheres to achieve rapid absorption, uniform distribution and prevention of reverse osmosis.

Benefits of technology

It improves the absorption performance and comfort, reduces the risk of side leakage, enhances the durability of the product and the comfort of the user, and meets the requirements of environmental protection and lightweight design.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a novel absorbent body for an environmentally friendly composite fiber sanitary napkin, as well as a preparation method and application thereof, belonging to the technical field of sanitary products. The absorbent body of the novel environmentally friendly composite fiber sanitary napkin comprises at least three layers of a fiber mesh structure, wherein the upper and lower surface layers are made of ES fiber, and the middle layer is made of bamboo-based modified viscose. The layers are tightly connected by microwave crosslinking, and the pore diameters of the upper, middle, and lower surface layers form a continuous gradient pore structure with gradually decreasing pore diameters. The absorbent body of the environmentally friendly composite fiber sanitary napkin prepared by the present invention has excellent water absorption, anti-reverse osmosis properties, and antibacterial durability, providing efficient, comfortable, and reliable care for users during menstruation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sanitary products, and in particular relates to an absorbent body of a novel environmentally friendly composite fiber sanitary napkin, a preparation method and an application thereof. Background Art

[0002] While some current improved sanitary napkin technologies have made some progress, they still have significant flaws that are difficult to ignore. Some products have indeed improved absorption rates by adopting new absorbent materials, such as improved formulas of super absorbent polymers (SAP). However, in actual use scenarios, due to the irrational design of their internal storage structures, the liquid cannot be effectively dispersed and stored after absorption, resulting in low storage space utilization. This makes it difficult to meet the needs of prolonged use at night or during heavy menstrual flow, forcing users to frequently change sanitary napkins, causing many inconveniences in their lives. In addition, the liquid storage structures of existing absorbent bodies mostly use fiber substrates with a single pore distribution, which causes the absorbed liquid to form localized high-pressure areas on the microscale, hindering the rapid penetration of subsequent liquids. At the same time, some products use low-density filling structures to reduce costs. Although they can temporarily accommodate liquids, their capillary effect is insufficient, making it difficult to form a stable water-locking gel, ultimately leading to a decrease in absorption efficiency.

[0003] Furthermore, some products simply increase the thickness of the absorbent layer to boost absorption. From the perspective of material mechanics and ergonomics, while this approach improves absorbency to a certain extent, it sacrifices the product's lightweightness and comfort. A thicker absorbent layer adds bulk and weight to the sanitary napkin, making it noticeably heavy and stuffy when worn, and increasing the sense of restraint during movement. This fails to meet the modern consumer's demand for lightweight, comfortable products and fails to meet the standards of high-quality, high-performance sanitary products. While thickening the absorbent layer can theoretically increase absorption capacity, it goes against the trend of "invisible" design in modern sanitary products. Research shows that for every 1mm increase in absorbent layer thickness, the user's perceived "foreign body sensation" increases by approximately 15%. More seriously, excessively thick designs can compromise the product's fit and create gaps, which in turn increases the risk of leakage, creating a vicious cycle of "increased absorbency, reduced comfort, and decreased safety."

[0004] The absorbent structure of existing sanitary napkins is prone to lateral leakage in dynamic environments, especially during movement or changes in body position. Due to the structural stability of the absorbent layer and insufficient flow-guiding design, liquid can diffuse laterally, leading to local saturation and overflow. Traditional products rely on a simple overlay of a surface flow-guiding layer and an absorbent layer, lacking the ability to actively control the three-dimensional distribution of liquid, making them difficult to adapt to the liquid management needs of complex usage scenarios. This structural flaw not only reduces product reliability but also increases the psychological burden on users.

[0005] Therefore, the present invention aims to provide a new type of absorbent body for environmentally friendly composite fiber sanitary napkins, which can achieve systematic optimization of the absorbent body function through innovative design, thereby solving the core problems of existing products such as poor absorption performance, low comfort, and easy side leakage. Summary of the Invention

[0006] The present invention aims to provide a novel absorbent body, preparation method, and application of an environmentally friendly composite fiber sanitary napkin. This invention aims to comprehensively address the core issues of existing products, such as poor absorption performance, low comfort, and lateral leakage. By optimizing material selection, innovating structural design, and improving the preparation process, this invention creates a sanitary product that provides efficient, comfortable, and reliable care for women during their menstrual period, significantly improving their quality of life and physical and mental comfort during their menstrual period.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a novel absorbent body for an environmentally friendly composite fiber sanitary napkin, comprising at least three layers of a fiber web structure, wherein the upper and lower surface layers are made of ES fibers, and the middle layer is made of bamboo-based modified viscose yarn. The layers are tightly connected by microwave cross-linking, and the pore diameter gradually decreases in the order of the upper surface layer, the middle layer, and the lower surface layer, forming a continuous gradient pore structure.

[0009] Preferably, the pore diameter of the upper surface layer is 50-100 μm, and the thickness of the upper surface layer is 0.3-0.5 mm. The pore diameter of the middle layer is 10-50 μm, and the thickness of the middle layer is 1.0-1.5 mm. The pore diameter of the lower surface layer is 5-10 μm, and the thickness of the lower surface layer is 0.5-0.8 mm.

[0010] Preferably, the fiber diameter of the ES fiber is 15-25 μm. The fiber diameter of the bamboo-based modified viscose yarn is 5-8 μm.

[0011] Preferably, the preparation method of the bamboo-based modified viscose yarn is:

[0012] The method comprises the following steps: taking bamboo fiber pulp, ultrasonically treating the pulp with alkali solution, and then wet spinning the bamboo fiber filaments with a diameter of 5-8 μm; grafting the sodium alginate solution and the bamboo fiber filaments with gamma rays under nitrogen protection to obtain the obtained product.

[0013] Preferably, the preparation method of the bamboo-based modified viscose yarn is:

[0014] Bamboo fiber pulp is ultrasonically treated in an alkaline solution, filtered, washed with water until neutral, and dried to obtain a pretreated material; an organic solvent is added to the pretreated material to prepare a spinning solution, and bamboo fiber filaments with a diameter of 5-8 μm are produced by wet spinning;

[0015] Sodium alginate solution was grafted onto bamboo fiber filaments under nitrogen protection by γ-ray irradiation to obtain bamboo-based modified viscose filaments.

[0016] Preferably, the alkali solution is at least one of a NaOH solution, a KOH solution, and a LiOH solution, and has a concentration of 5-7 wt%.

[0017] Preferably, the frequency of the ultrasonic treatment is 30-50 kHz and the time of the ultrasonic treatment is 20-40 min.

[0018] Preferably, the process conditions of the wet spinning include:

[0019] Preferably, the concentration of bamboo fiber pulp in the spinning solution is 10-15wt%, and the organic solvent is carbon disulfide.

[0020] Preferably, the aging time of the spinning solution is 8-12 hours; the aging temperature is room temperature.

[0021] Preferably, the coagulation bath for wet spinning is an aqueous solution consisting of sulfuric acid and sodium sulfate, wherein the concentration of sulfuric acid is 5-8wt% and the concentration of sodium sulfate is 12-15wt%; and the temperature of the coagulation bath is 45-55°C.

[0022] Preferably, during the wet spinning process, the stretching ratio is 3-5 times.

[0023] Preferably, the concentration of the sodium alginate solution is 2-4 wt %.

[0024] Preferably, the dose range of the radiation grafting is 20-30 kGy; and the reaction temperature of the radiation grafting is room temperature.

[0025] Compared with existing ordinary viscose yarn, the bamboo fiber-based modified viscose yarn of the present invention shows significant advantages in raw material properties, functional properties, and structural matching. These advantages can comprehensively improve the performance of sanitary napkins.

[0026] The present invention adopts ultrasonic assisted alkali treatment process to refine the bamboo fiber diameter from 20-30μm to 5-8μm, and increase the specific surface area to 150m 2 / g.

[0027] Advantages of raw material characteristics: Ordinary viscose yarn relies on wood pulp as raw material. The production of each ton of fluff pulp consumes 2.5 tons of wood, which consumes a lot of forest resources. However, bamboo fiber-based modified viscose yarn uses bamboo fiber as raw material, which is widely available and renewable, and is more in line with environmental protection concepts. In terms of fiber physical properties, ordinary viscose yarn has a thick fiber diameter (10-15μm) and a low specific surface area (≤80m 2 / g), bamboo fiber-based modified viscose yarn is treated with ultrasonic assisted alkali process, the fiber diameter is refined to 5-8μm, and the specific surface area is increased to 150m2 / g, which greatly increases the contact area with the liquid and improves the liquid absorption capacity.

[0028] Functional Advantages: Ordinary viscose yarn lacks natural antibacterial properties, while bamboo fiber-based modified viscose yarn utilizes free radical polymerization to graft sodium alginate onto the fiber surface. It then utilizes an in-situ reduction method to load chitosan-coated nanosilver, achieving broad-spectrum antibacterial properties. The antibacterial rate against Escherichia coli and Staphylococcus aureus exceeds 99.8%, effectively inhibiting bacterial growth and ensuring menstrual hygiene and health. Through grafting modification and structural optimization, the hydrophilicity of bamboo fiber-based modified viscose yarn is enhanced. In the gradient sandwich structure of the sanitary napkin, the hydrophobicity of the bamboo fiber-based modified viscose yarn in the middle layer complements that of the ES fiber, facilitating the transfer and storage of liquids within the sanitary napkin and improving overall absorption performance.

[0029] Structural Compatibility Advantage: In this invention's gradient sandwich sanitary napkin, bamboo fiber-based modified viscose yarn is located in the middle layer. Its fiber diameter of 5-8μm and pore diameter of 10-50μm complement the pore sizes of the surface and lower surface layers to form a continuous gradient pore structure. This structure facilitates rapid liquid transfer from the surface layer to the middle layer for storage, while preventing reverse osmosis in the lower surface layer. Conventional viscose yarn, due to its inherent properties, struggles to achieve such efficient structural coordination, resulting in poor liquid diffusion uniformity and prone to localized saturation.

[0030] Graft modification: Sodium alginate (molecular weight 80kDa) was grafted onto the fiber surface by free radical polymerization, with a grafting rate of 12-15% (confirmed by FTIR spectrum at 1650cm -1 Appear characteristic peaks).

[0031] Graft modification is a key step in the processing of bamboo fiber-based modified viscose yarn. It improves the fiber performance in terms of hydrophilicity, antibacterial properties and structural stability, thereby enhancing the overall function of sanitary napkins. The specific purposes are as follows:

[0032] Enhanced hydrophilicity: Sodium alginate (molecular weight 80kDa) is grafted onto the fiber surface through free radical polymerization. Sodium alginate contains numerous hydrophilic groups. These groups increase the hydrophilicity of the bamboo fiber-based modified viscose yarn. During the absorption of menstrual blood, this enhanced hydrophilicity helps the fiber absorb and transfer fluid more quickly, increasing the napkin's absorption rate and enabling it to more quickly absorb and disperse menstrual blood, maintaining a dry surface.

[0033] Improved antibacterial properties: Grafting modification doesn't directly achieve antibacterial properties, but it creates favorable conditions for subsequent functional loading. The grafted fiber surface forms a unique structure that facilitates the in-situ reduction loading of chitosan-coated silver nanoparticles (Ag particle size 20-50nm, loading ≥0.2wt%). This achieves broad-spectrum antibacterial activity, with inhibition rates exceeding 99.8% against Escherichia coli and Staphylococcus aureus. Grafting modification is a crucial foundation for efficient loading of antibacterial ingredients, indirectly enhancing the fiber's antibacterial properties and ensuring menstrual hygiene.

[0034] Optimizing Interfiber Interactions: Grafting modification alters the physical and chemical properties of the fiber surface to a certain extent, changing the interactions between the fibers. During microwave crosslinking, the grafted fibers are able to better bond with other fibers (such as ES fibers), enhancing interlayer bonding. In the resulting gradient composite structure, the grafted viscose fibers in the middle layer closely cooperate with the ES fibers in the upper and lower layers, helping to form a stable continuous gradient pore structure, improving the structural stability and performance of the entire sanitary napkin absorbent.

[0035] Preferably, the absorbent of the novel environmentally friendly composite fiber sanitary napkin further comprises a functional additive.

[0036] Preferably, the functional auxiliary agent comprises chitosan-coated nanosilver.

[0037] Chitosan-coated silver nanoparticles form a core-shell structure through the coordination of chitosan amino groups with silver nanoparticles. Chitosan acts as a coating layer, stabilizing the silver nanoparticles and enhancing their antibacterial synergistic effect.

[0038] Preferably, the preparation method of the chitosan-coated nanosilver is:

[0039] The in-situ reduction method is used for preparation, and the specific steps are as follows:

[0040] Dissolve chitosan in acetic acid solution, add silver nitrate solution and stir to form a precursor;

[0041] Sodium borohydride is added dropwise to the precursor to initiate a reduction reaction, thereby obtaining chitosan-coated nanosilver.

[0042] Preferably, the preparation method of the chitosan-coated nanosilver is:

[0043] Dissolve chitosan in 0.5-1.5% acetic acid solution to obtain a chitosan solution with a concentration of 0.5-1.5 wt%, adjust the pH to 5.5-6.0, add silver nitrate solution (AgNO3, concentration 0.02-0.08 M), and stir for 20-40 minutes to form a precursor;

[0044] Sodium borohydride (NaBH4, concentration 0.05-0.2M) is added to the precursor to initiate a reduction reaction to generate chitosan-coated nanosilver; unreacted substances are removed by centrifugation and washing, and the precursor is freeze-dried to obtain chitosan-coated nanosilver powder.

[0045] Preferably, the molar ratio of AgNO3 to chitosan is 1:2-1:5, and the particle size of the nanosilver is controlled to be 20-50 nm.

[0046] The amino groups of chitosan coordinate with silver ions to prevent nanosilver from agglomerating and enhance stability.

[0047] Chitosan itself has antibacterial properties and forms a synergistic antibacterial effect with nanosilver.

[0048] Controllable particle size: By adjusting the ratio of AgNO3 to chitosan, the nanosilver particle size is controlled to be 20-50nm and the chitosan coating layer thickness is 5-10nm.

[0049] Enhanced stability: amino groups of chitosan Coordinates with silver ions to prevent nanosilver aggregation (Zeta potential +25mV).

[0050] Antibacterial synergy: Chitosan itself has antibacterial properties and forms a synergistic effect with nanosilver.

[0051] XPS analysis showed that the Ag3d peak was at 415.8 eV (metallic state) and the N1s peak was at 399.2 eV (chitosan amino group).

[0052] TEM showed that the nanosilver particle size was 20-50nm and the chitosan coating layer thickness was 5-10nm; XPS confirmed that Ag was in metallic state (Ag3d peak position 415.8eV) and chitosan amino groups existed (N1s peak position 399.2eV).

[0053] Antibacterial performance: The antibacterial rate against Escherichia coli is greater than 99.8%, and is still greater than 95% after 50 water washings (the antibacterial agent of traditional process loses effectiveness after 5 water washings).

[0054] The in-situ synthesis of the present invention avoids organic solvent pollution of purchased nanosilver, is environmentally friendly, and complies with the concept of green production.

[0055] Independent synthesis can precisely control the particle size and loading amount of nanosilver, ensuring interfacial bonding with bamboo fiber-based modified viscose yarn and improving antibacterial durability.

[0056] Chitosan-coated nanosilver is independently synthesized by the in-situ reduction method. It has the advantages of controllable particle size, high stability and low cost. It works synergistically with the grafted structure of bamboo fiber-based modified viscose to achieve long-lasting antibacterial function.

[0057] Preferably, the functional auxiliary agent further includes temperature-sensitive hydrogel microspheres.

[0058] Preferably, the thermosensitive hydrogel microspheres are composed of N-isopropylacrylamide and acrylic acid copolymers encapsulating aloe extract.

[0059] Preferably, the molar ratio of N-isopropylacrylamide to acrylic acid is 7-9:2.

[0060] Preferably, the concentration of the embedded aloe extract in the thermosensitive hydrogel microspheres is 7-12%.

[0061] Preferably, the functional additive is composed of chitosan-coated nanosilver and thermosensitive hydrogel microspheres in a weight ratio of 1:0.5-2.

[0062] Thermosensitive hydrogel microspheres can improve the breathability of sanitary napkins, relieve the feeling of stuffiness, and also have certain care effects, bringing users a more comfortable and healthy use experience.

[0063] Enhanced Breathability: The thermosensitive hydrogel microspheres have a lower critical solution temperature (LCST) of 34.5°C. At body temperature, the porosity of the microspheres expands from 50nm to 120nm, increasing air permeability by 15%. During use, body temperature causes the microsphere pores to expand, allowing air to circulate more freely. This effectively improves air circulation within the sanitary napkin, allowing moisture to escape quickly, reducing the stuffiness caused by airtightness and providing greater comfort.

[0064] Assisting liquid absorption and transport: Hydrogel microspheres have a certain water absorption capacity, which can help absorb some of the liquid when the sanitary napkin absorbs menstrual blood. When the porosity of the microspheres increases, it not only facilitates gas exchange but also provides more channels for liquid transport within the sanitary napkin, helping menstrual blood diffuse and penetrate between the different structural layers of the sanitary napkin, making the liquid more evenly distributed, avoiding local saturation, and improving the overall absorption performance of the sanitary napkin.

[0065] Providing skin-care benefits: The thermosensitive hydrogel microspheres are composed of N-isopropylacrylamide (NIPAM) and acrylic acid (AA) copolymers encapsulating aloe vera extract. Aloe vera extract has numerous skin-beneficial properties, such as anti-inflammatory, soothing, and moisturizing. During use, these ingredients are slowly released, providing a caring effect on the skin of women's intimate areas, reducing the risk of skin irritation and discomfort, and enhancing safety and comfort.

[0066] A method for preparing an absorbent body of a novel environmentally friendly composite fiber sanitary napkin comprises the following steps:

[0067] The upper surface layer is made of ES fiber, the middle layer is made of bamboo-based modified viscose yarn, and the lower surface layer is made of ES fiber. They are laid in the processing area of ​​the preheated microwave cross-linking equipment in this order, and then microwave cross-linked under the action of microwaves and magnetic fields and axial pressure is applied, and then cooled. The fiber web after microwave cross-linking is impregnated with an aqueous solution of functional additives, the excess solution is squeezed out, and the web is dried to obtain the absorbent body of a new environmentally friendly composite fiber sanitary napkin.

[0068] Preferably, the preheating is to 83-87°C.

[0069] Preferably, the power of the microwave is 200-400W, and the time is 10-15s.

[0070] Preferably, the magnetic field strength is 0.1-0.5T.

[0071] Preferably, the axial pressure refers to a vertical pressure applied to the flat fiber layer perpendicular to the surface of the fiber web; the magnitude of the axial pressure is 0.05-0.1 MPa.

[0072] Preferably, the immersion time is 10-30 minutes.

[0073] Preferably, the drying temperature is 60-80°C.

[0074] Preferably, the concentration of chitosan-coated nanosilver in the functional additive aqueous solution is 0.1-0.3%.

[0075] Preferably, the weight ratio of the thermosensitive hydrogel microspheres to the chitosan-coated nanosilver is 0.5-2:1.

[0076] Preferably, the concentration of the temperature-sensitive hydrogel microspheres in the functional additive aqueous solution is 0.1-0.3%.

[0077] The present invention realizes the continuous transition of interlayer gradient pores through microwave cross-linking (including axial pressure), thereby avoiding pore blockage caused by traditional adhesives.

[0078] The characteristics of each layer of the absorbent body of the present invention are as follows:

[0079] Loose structure on the upper surface (50-100μm pores): ES fibers are melt-bonded under low axial pressure, retaining large-aperture channels for rapid flow diversion.

[0080] Intermediate layer transition structure (10-50μm pores): After ultrasonic refinement, bamboo fibers form a microporous network. The hydrophilicity of grafted sodium alginate promotes the lateral diffusion of liquid and regulates liquid distribution. At the interface between bamboo fibers and ES fibers in the microwave field, the molten ES fibers fill the gaps between bamboo fibers, forming a pore gradient.

[0081] Dense structure of the lower surface (5-10μm pores): ES fibers completely melt under high axial pressure to form a dense barrier, which, combined with the nano-silver antibacterial layer, inhibits liquid reverse osmosis.

[0082] Synergistic mechanism of microwave cross-linking and axial pressure.

[0083] Effect of microwave field:

[0084] Molecular excitation: 2.45GHz microwaves excite polar groups of fiber molecules (such as -OH, ) High-frequency vibration generates internal heat.

[0085] ES fiber melting: Microwaves selectively melt the ES fiber sheath (PE) at 83-87°C to form bonding sites.

[0086] Bamboo fiber activation: Microwaves accelerate the chemical bonding (such as ester bond, hydrogen bond) between bamboo fiber grafting groups (sodium alginate) and ES fibers.

[0087] Axial pressure effect:

[0088] Interlayer densification: 0.05-0.1MPa pressure compresses the gaps between the fiber layers, allowing the molten ES fibers to penetrate into the pores of the bamboo fiber layer.

[0089] Gradient pore design:

[0090] Surface layer (ES fiber layer): large pores (50-100μm) for rapid absorption;

[0091] Middle layer (bamboo-based modified viscose): medium pores (10-50μm) are used for liquid transmission and storage; lower surface layer (ES fiber layer): small pores (5-10μm) form an anti-reverse osmosis barrier.

[0092] Structural-functional linkage: Microwave cross-linking (including axial pressure) achieves a continuous transition of interlayer gradient pores, avoiding pore blockage caused by traditional adhesives; the grafted modified viscose thread in the middle layer (grafting rate 12-15%) enhances hydrophilicity and antibacterial properties, complementing the hydrophobicity of ES fibers.

[0093] Effect of microwave cross-linking process on structure:

[0094] Before microwave cross-linking:

[0095] ES layer-bamboo base-ES layer; loosely stacked, with blurred boundaries between layers;

[0096] After microwave cross-linking (+ axial pressure):

[0097] ES layer-bamboo base layer-ES layer; fiber bonding, pore gradient continuous transition.

[0098] Axial pressure: compresses the gaps between fibers and cooperates with microwaves to excite molecular chains to form a stable chemically bonded network.

[0099] Gradient pore control: The pressure gradient (light pressure on the upper surface → medium pressure in the middle layer → heavy pressure on the lower surface) cooperates with the difference in fiber diameter (ES fiber 15-25μm, bamboo fiber 5-8μm) to form a continuous pore gradient.

[0100] The “light pressure on the upper surface → medium pressure on the middle layer → heavy pressure on the lower surface” is not a physical layered pressure application, but a natural formation of pressure distribution differences during the cross-linking process by controlling the magnitude and action time of the axial pressure and combining the physical properties of the fiber layer (such as thickness and pore diameter).

[0101] The present invention is directly driven by microwave power enhancement and combines the synergistic effect of magnetic field and axial pressure to achieve efficient cross-linking and gradient pore control.

[0102] Material property driven pressure distribution:

[0103] Middle layer (bamboo fiber layer): The thickness is larger (1.0-1.5mm) and the fiber diameter is finer (5-8μm). It is more easily compressed under the overall pressure, resulting in a higher effective pressure actually borne by the middle layer.

[0104] Upper and lower surface layers (ES fiber layers): thinner (0.3-0.5mm and 0.5-0.8mm) and coarser fibers (15-25μm), with a lower degree of compression under the same pressure, resulting in a "light pressure" effect.

[0105] Functional synergy: The dynamic response of the nanosilver antibacterial layer and the thermosensitive hydrogel microspheres forms a double barrier of sanitary protection.

[0106] The present invention uses Micro-CT scanning to show that the diameter of the interlayer pores decreases continuously from the surface layer (50-100 μm) to the middle layer (10-50 μm) and then to the lower surface layer (5-10 μm), proving the effectiveness of the pressure gradient.

[0107] The liquid diffusion test of the present invention shows that the diffusion speed of the product of the present invention is significantly higher than that of traditional products, verifying the transmission efficiency of the gradient pores.

[0108] The present invention also discloses the application of the absorbent body of the novel environmentally friendly composite fiber sanitary napkin in the preparation of sanitary napkins, incontinence nursing pads and medical dressings.

[0109] The absorbent body has a thickness of 0.8-1.2 mm, a bending stiffness of ≤50 mN·cm, and an air permeability of ≥950 cm 3 / (cm 2 ·s).

[0110] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0111] Compared with the traditional hot air process, the microwave cross-linking process adopted in the present invention has obvious advantages in energy consumption, temperature control, and bonding effect, thereby improving product performance and production efficiency.

[0112] Designed based on material characteristics: Bamboo fiber-based modified viscose and ES fiber possess different physical and chemical properties. After refinement, bamboo fiber-based modified viscose has a large specific surface area and contains reactive groups. ES fiber undergoes changes such as melting at certain temperatures. The microwave crosslinking process utilizes microwave energy to rapidly vibrate and rotate these fiber molecules, promoting molecular chain movement and achieving crosslinking under mild conditions, thus preventing high temperatures from damaging fiber properties. This technology is tailored to the material's characteristics, aligning with the antibacterial properties of the bamboo fiber-based modified viscose without compromising its functional performance.

[0113] Significantly Reduced Energy Consumption: While traditional hot air processes consume ≥120kWh / ton of product, microwave cross-linking technology consumes only 45kWh / ton, a 62.5% reduction. Microwave heating is an internal heating method that acts directly on the material, allowing it to rapidly absorb energy and achieve cross-linking. This reduces energy loss during transmission and heating, lowering production costs and aligning with industry trends toward energy conservation and emission reduction.

[0114] Good temperature uniformity: Traditional hot air processes suffer from poor temperature uniformity, fluctuating within ±8°C. Microwave crosslinking technology, however, achieves temperature uniformity of ±1.5°C, an 81% improvement. A microwave field control algorithm precisely controls microwave power and dynamic pressure compensation to ensure temperature stability during the crosslinking process. This results in more uniform fiber crosslinking, avoids variations in bond strength caused by temperature fluctuations, and improves product quality consistency.

[0115] High Bond Strength: Microwave crosslinking technology achieves a bond strength of 25 N / cm, a 39% improvement over the 18 N / cm achieved with traditional hot air crosslinking. The synergistic effect of microwaves' rapid heating and axial pressure creates closer contact between fibers, promoting chemical bonding and enhancing interlayer cohesion. This helps maintain structural integrity during use, preventing delamination and breakage, and improving product durability and reliability. DETAILED DESCRIPTION

[0116] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0117] Example 1

[0118] This embodiment provides a new type of environmentally friendly composite fiber sanitary napkin absorbent body, including a three-layer fiber mesh structure, wherein the upper surface layer and the lower surface layer are made of ES fiber, and the middle layer is made of bamboo-based modified viscose yarn. The layers are arranged in the order of upper surface layer, middle layer, and lower surface layer, and the layers are cross-linked by microwaves to form a tightly connected structure.

[0119] The pore diameter of the upper surface layer is 60 μm; the thickness of the upper surface layer is 0.4 mm; the rapid liquid conduction layer needs to be thin and dense to ensure rapid liquid penetration while maintaining a soft touch;

[0120] The pore diameter of the intermediate layer is 20 μm; the thickness of the intermediate layer is 1.2 mm; high liquid storage requirements require a larger thickness, and gradient pores are used to achieve efficient liquid storage;

[0121] The pore diameter of the lower surface layer is 6 μm; the thickness of the lower surface layer is 0.6 mm; the anti-reverse osmosis layer requires a moderate thickness to ensure density while maintaining air permeability;

[0122] The overall absorbent body thickness is ≤2.2mm, which meets the standard of ultra-thin sanitary napkins (the industry standard is ≤3mm);

[0123] The ES fiber has a fiber diameter of 20 μm;

[0124] The fiber diameter of the bamboo-based modified viscose yarn is 6 μm.

[0125] The preparation method of the bamboo-based modified viscose yarn is:

[0126] Bamboo fiber pulp (degree of polymerization 650) was ultrasonically treated with a 6% NaOH solution at 40 kHz for 30 minutes, filtered, washed with water until neutral, and dried to obtain a pretreated material; an organic solvent was added to the pretreated material to prepare a spinning solution, and bamboo fiber filaments with a diameter of 6 μm were produced by wet spinning;

[0127] Sodium alginate solution was grafted onto bamboo fiber filaments by γ-ray irradiation under nitrogen protection, with a grafting rate of 13.2%, to obtain bamboo-based modified viscose filaments.

[0128] The concentration of bamboo fiber pulp in the spinning solution is 12wt%, and the organic solvent is carbon disulfide;

[0129] The aging time of the spinning solution is 10 h, and the aging temperature is room temperature;

[0130] The coagulation bath of the wet spinning process is an aqueous solution composed of sulfuric acid and sodium sulfate; wherein the concentration of sulfuric acid is 6wt% and the concentration of sodium sulfate is 14wt%; the temperature of the coagulation bath is 50°C;

[0131] During the wet spinning process, the draw ratio was 4 times;

[0132] The concentration of the sodium alginate solution is 3wt%;

[0133] The irradiation dose was 25 kGy, and the reaction temperature of the irradiation grafting was room temperature.

[0134] The absorbent of the novel environmentally friendly composite fiber sanitary napkin also includes functional additives.

[0135] The functional additive consists of chitosan-coated nanosilver and thermosensitive hydrogel microspheres in a weight ratio of 1:1.

[0136] The preparation method of the chitosan-coated nanosilver is as follows:

[0137] Chitosan was dissolved in 1% acetic acid solution to obtain a 1 wt% chitosan solution (deacetylation degree ≥ 90%, average molecular weight 200 kDa), the pH was adjusted to 5.8, and silver nitrate solution (AgNO3, concentration 0.05 M) was added and stirred for 30 min to form a precursor;

[0138] Sodium borohydride (NaBH4, 0.1 M) was added to the precursor to initiate a reduction reaction, generating chitosan-coated silver nanoparticles. The resulting mixture was centrifuged (8000 rpm, 10 min), washed to remove unreacted material, and freeze-dried to obtain chitosan-coated silver nanoparticle powder. The molar ratio of AgNO3 to chitosan was 1:3.

[0139] The thermosensitive hydrogel microspheres are composed of aloe vera extract embedded in a copolymer of N-isopropylacrylamide and acrylic acid, wherein the molar ratio of N-isopropylacrylamide to acrylic acid is 8:2, and the concentration of the embedded aloe vera extract in the thermosensitive hydrogel microspheres is 10%.

[0140] A method for preparing an absorbent body of a novel environmentally friendly composite fiber sanitary napkin comprises the following steps:

[0141] Step 1: Preheat the microwave cross-linking equipment (with magnetic field function) to 85°C;

[0142] Step 2: Evenly lay the fiber web in the preheated microwave crosslinking equipment in the order of ES fiber for the upper surface layer, bamboo-based modified viscose yarn for the middle layer, and ES fiber for the lower surface layer; wherein the weight ratio of ES fiber to bamboo-based modified viscose yarn is 3:7;

[0143] Step 3: Start the microwave cross-linking equipment, set the power to 300W, the time to 12s, and start the magnetic field function at the same time, ensuring that the magnetic field strength is within the range of 0.1-0.5T; under the combined action of microwaves and magnetic fields, apply axial pressure, ensuring that the axial pressure is within the range of 0.05-0.1MPa, and allow the fiber web to undergo microwave cross-linking reaction at 85°C; after cross-linking is completed, turn off the microwave and magnetic field, remove the fiber web, and naturally cool it to room temperature;

[0144] Step 4: Immerse the cross-linked fiber mesh in the functional additive aqueous solution for 20 minutes to ensure complete saturation, remove the fiber mesh, and gently squeeze to remove excess solution; dry the immersed fiber mesh at 70°C until completely dry; the functional additive aqueous solution contains 0.2% chitosan-coated nanosilver and 0.2% thermosensitive hydrogel microspheres;

[0145] Step 5: Perform a performance test on the treated fiber web, package the qualified fiber web, and store it in a dry and cool place to obtain the absorbent body of the new environmentally friendly composite fiber sanitary napkin.

[0146] Under the above thickness combination, the liquid diffusion rate reaches 4.2mm / s (1.8mm / s for traditional structure), the uniformity index is 0.92 (0.65 for traditional process); the bending stiffness is ≤50mN·cm (ASTMD790 test to ensure flexibility); the interlayer interface is tightly bonded, and the pore connectivity rate is >90%.

[0147] The above thickness parameter combination achieves an optimal balance of liquid absorption, liquid storage and anti-seepage performance through the synergistic effect of gradient pores and materials, which is in line with one of the technical cores of the present invention.

[0148] Comparative Example 1

[0149] The only difference from Example 1 is that the microwave cross-linking process is replaced by a traditional hot air process, as follows:

[0150] Step 1: Preheat the hot air circulation equipment to 110°C to ensure that the temperature inside the equipment is uniform and stable;

[0151] Step 2: Evenly lay the fiber web in the processing area of ​​the preheated hot air circulation equipment in the order of ES fiber for the upper surface layer, bamboo-based modified viscose yarn for the middle layer, and ES fiber for the lower surface layer; wherein the weight ratio of ES fiber to bamboo-based modified viscose yarn is 3:7;

[0152] Step 3: Start the hot air circulation equipment, set the wind speed to 3m / s and the processing time to 5min, ensure that the hot air blows evenly on the surface of the fiber web, and hot air consolidate the fiber web at 110℃; after completion, turn off the equipment, take out the fiber web, and let it cool naturally to room temperature;

[0153] Step 4: Immerse the fiber mesh in the functional additive aqueous solution for 20 minutes to ensure complete saturation, remove the fiber mesh, and gently squeeze to remove excess solution; dry the immersed fiber mesh at 70°C until completely dry; the functional additive aqueous solution has a concentration of 0.2% chitosan-coated nanosilver and a concentration of 0.2% thermosensitive hydrogel microspheres;

[0154] Step 5: Perform a performance test on the treated fiber web, package the qualified fiber web, and store it in a dry and cool place to obtain the absorbent body of the composite fiber sanitary napkin.

[0155] Comparative Example 2

[0156] The only difference from Example 1 is that the bamboo-based modified viscose yarn is replaced by ordinary viscose yarn, specifically as follows: the fiber diameter of the ordinary viscose yarn is 12 μm, the specific surface area is 70 m 2 / g.

[0157] Comparative Example 3

[0158] The only difference from Example 1 is that the chitosan-coated nanosilver is replaced by a mixture of AgNO 3 and chitosan in a molar ratio of 1:3.

[0159] Comparative Example 4

[0160] The only difference from Example 1 is that the composition of the functional additive is different, specifically as follows: the functional additive is chitosan-coated nanosilver.

[0161] (1) Advantages of microwave cross-linking process

[0162] Table 1: Process comparison

[0163] Technical elements Example 1 Microwave cross-linking process Comparative Example 1 Hot Air Process Bonding mechanism Microwave internal heating + magnetic field orientation + pressure densification Thermal conduction melting Pore ​​control Gradient pores, continuous transition Random pores, easy to clog Functional load Magnetic field assisted in-situ fixation, long-lasting antibacterial Surface adsorption, easy to fall off Energy consumption 45kWh / ton (-62.5%) 120kWh / ton Temperature uniformity ±8℃(81%↑) ±1.5℃ Bond strength 18N / cm (+39%) 25N / cm

[0164] (2) Clinical evaluation

[0165] Subjects: 300 female volunteers (aged 18-45 years old), used for 3 consecutive months.

[0166] Results statistics:

[0167] The incidence of skin irritation of the present invention is 0.3% (4.7% for the product in Comparative Example 1);

[0168] The complaint rate of the present invention for feeling stuffy is 1.2% (22% for the product in Comparative Example 1);

[0169] The incidence of nighttime side leakage of the present invention is 0% (15% for the product in comparative example 1).

[0170] (3) Performance testing

[0171] Table 2: Performance Test

[0172] Test standards Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Water absorption rate / mL / s GB / T24218.6-2010 4.1 1.2 1.8 3.7 2.4 Reverse osmosis amount / g ISO11948-1:1996 0.03 0.28 0.22 0.08 0.13 Air permeability / cm³ / (cm²·s) ASTM D737-2018 980 420 660 820 750 Degradation rate (180 days) / % ISO14855-1:2012 93.5 43.0 72.0 92.8 90.6 Antibacterial rate (Escherichia coli) / % GB / T15979-2002 99.9 98.7 98.2 62.6 99.0 Antibacterial durability / % The antibacterial rate was measured after washing 50 times 95.1 52.3 64.0 35.5 87.2

[0173] From the above performance test results, it can be seen that the absorbent of the new environmentally friendly composite fiber sanitary napkin prepared in Example 1 not only has good absorbency, impermeability, and breathability, but also has excellent antibacterial properties, antibacterial durability (water-resistant), and environmental protection. This is because the present invention uses ES fiber and bamboo-based modified viscose yarn as raw materials, processed by a specific microwave crosslinking process, and also adds chitosan-coated nanosilver and thermosensitive hydrogel microspheres as functional additives, which work synergistically to further improve the comprehensive performance of the absorbent. Compared with Example 1, Comparative Example 1 only uses the traditional hot air process, Comparative Example 2 only uses ordinary viscose yarn, Comparative Example 3 does not use chitosan-coated nanosilver, and Comparative Example 4 does not use thermosensitive hydrogel microspheres. As can be seen from the results, it leads to a certain degree of decline in the various properties of the composite fiber sanitary napkin absorbent material, which proves the importance of the technical solution defined in the present invention for its technical effect.

[0174] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A novel absorbent body of an environmentally friendly composite fiber sanitary napkin, characterized in that: The fiber mesh structure comprises at least three layers, wherein the upper and lower surface layers are made of ES fibers, and the middle layer is made of bamboo-based modified viscose. The layers are closely connected by microwave cross-linking, and the pore diameter gradually decreases in the order of the upper surface layer, the middle layer, and the lower surface layer, forming a continuous gradient pore structure. The preparation method of bamboo-based modified viscose yarn comprises the following steps: taking bamboo fiber pulp, ultrasonically treating it with alkali solution, and wet spinning it to obtain bamboo fiber yarn; grafting the bamboo fiber yarn with sodium alginate solution by gamma ray irradiation under nitrogen protection to obtain the modified viscose yarn; The absorber also includes a functional additive; the functional additive includes nanosilver@chitosan; the preparation method of nanosilver@chitosan is: dissolving chitosan in acetic acid solution, adding silver nitrate solution and stirring to form a precursor; adding sodium borohydride to the precursor, and in situ reduction to obtain nanosilver@chitosan; the molar ratio of silver nitrate to chitosan is 1:2-1:5, the nanosilver particle size is 20-50nm, and the chitosan coating layer thickness is 5-10nm.

2. The absorbent body of the novel environmentally friendly composite fiber sanitary napkin according to claim 1, characterized in that: The pore diameter of the upper surface layer is 50-100μm; the thickness of the upper surface layer is 0.3-0.5mm; the pore diameter of the middle layer is 10-50μm; the thickness of the middle layer is 1.0-1.5mm; the pore diameter of the lower surface layer is 5-10μm; the thickness of the lower surface layer is 0.5-0.8mm; the fiber diameter of the ES fiber is 15-25μm; the fiber diameter of the bamboo-based modified viscose yarn is 5-8μm.

3. The absorbent body of the novel environmentally friendly composite fiber sanitary napkin according to claim 1, characterized in that: The coagulation bath of wet spinning is an aqueous solution composed of sulfuric acid and sodium sulfate, wherein the concentration of sulfuric acid is 5-8wt%, the concentration of sodium sulfate is 12-15wt%; the concentration of sodium alginate solution is 2-4wt%; and the dose range of irradiation grafting is 20-30kGy.

4. The absorbent body of the novel environmentally friendly composite fiber sanitary napkin according to claim 1, characterized in that: The functional additives also include thermosensitive hydrogel microspheres; the thermosensitive hydrogel microspheres are composed of N-isopropylacrylamide and acrylic acid copolymers embedding aloe vera extract; the concentration of the embedded aloe vera extract is 7-12%.

5. The method for preparing the absorbent body of the novel environmentally friendly composite fiber sanitary napkin according to any one of claims 1 to 4, characterized in that: The following steps are involved: The upper surface layer is made of ES fiber, the middle layer is made of bamboo-based modified viscose yarn, and the lower surface layer is made of ES fiber. They are laid in the processing area of ​​the preheated microwave cross-linking equipment in this order, and then microwave cross-linked under the action of microwaves and magnetic fields and axial pressure is applied, and then cooled. The fiber web after microwave cross-linking is impregnated with an aqueous solution of functional additives, the excess solution is squeezed out, and the web is dried to obtain the absorbent body of a new environmentally friendly composite fiber sanitary napkin.

6. The method for preparing the absorbent body of the novel environmentally friendly composite fiber sanitary napkin according to claim 5, characterized in that: Preheat to 83-87°C; microwave power is 200-400W, time is 10-15s; magnetic field strength is 0.1-0.5T; axial pressure is 0.05-0.1MPa.

7. Use of the absorbent body of the novel environmentally friendly composite fiber sanitary napkin according to any one of claims 1 to 4 in the preparation of sanitary napkins, incontinence care pads or medical dressings.

Citation Information

Patent Citations

  • Super-absorbent fiber multi-layer gradient structure absorbent core layer

    CN111568645A

  • Preparation method of liquid cotton absorber and sanitary towel thereof

    CN118697555A